Adrenergic Tone as an Intermediary in the Temperament Syndrome Associated With Flight Speed in Beef Cattle - Colditz, Ian G. (Frontiers in Animal Science, 2021)
The temperament of farm animals can influence their resilience to everyday variations within the managed production environment and has been under strong direct and indirect selection during the course of domestication. A prominent objective measure used for assessing temperament in beef cattle is the behavioral flight response to release from confinement in a crush or chute. This behavioral measure, termed flight speed (also known as escape velocity) is associated with physiological processes including body temperature, feeding behavior, growth rate, carcass composition, immune function and health outcomes. This review examines the functional links between this suite of traits and adrenergic activity of the sympathetic nervous system and the adrenomedullary hormonal system. It is suggested that flight speed is the behavioral aspect of an underlying “flightiness” temperament syndrome, and that elevated adrenergic tone in animals with a high level of flightiness (i.e. flighty animals) tunes physiological activities towards a sustained “fight or flight” defense profile that reduces productivity and the capacity to flourish within the production environment. Nonetheless, despite a common influence of adrenergic tone on this suite of traits, variation in each trait is also influenced by other regulatory pathways and by the capacity of tissues to respond to a range of modulators in addition to adrenergic stimuli. It is suggested that tuning by adrenergic tone is an example of homeorhetic regulation that can help account for the persistent expression of behavioral and somatic traits associated with the flight speed temperament syndrome across the life of the animal. At a population level, temperament may modulate ecological fit within and across generations in the face of environmental variability and change. Associations of flight speed with the psychological affective state of the animal, and implications for welfare are also considered. The review will help advance understanding of the developmental biology and physiological regulation of temperament syndromes.